THE ROLE OF SEMICONDUCTOR MATERIALS IN THE DEVELOPMENT OF SCIENCE AND TECHNOLOGY - Turaev Ergash Yuldashovich; Karimova Shahlo Eshnazar kizi (Galaxy International Interdisciplinary Research Journal, 2021)
This article dicsusses the role of semiconductor materials in the development of modern science and technology.